Metode Inverse Kinematics Dan Frame-By-Frame Pada Simulasi Jalan Laba-Laba - Laras Niti Mulyani; Suhendro Yusuf; Sriyanto Sriyanto (Manutech : Jurnal Teknologi Manufaktur, 2023)
Animation technique can be applied as a whole to the film or a combination of animation with the real world. Animated animal movements can look more realistic if they are based on real animal movements. The Nephila Iraunata spider has eight legs and a unique walking pattern. The method employed in the animation Spider joints was the inverse kinematics method. Animated Spider's walking pattern refers to the original walking pattern by using the frame-by-frame method. The design consisted of 3D character creation, Rigging, frame-by-frame animation, and motion implementation. Each base of the foot was measured using a protractor to determine the degrees of freedom. Character model created by using the Autodesk Maya application. Character rigging adjusted to the original Spider's body shape. The application of Inverse Kinematics used the Unity application with a focus on the base bone to the toe and adjusted according to the value of degrees of freedom. The curve of the original base bone angle with animation was compared using a tracker application to find out the level of similarity. Based on the results of the respondent’s responses, the level of accuracy of the spider animation is similar to the original spider (81.7%).